Environmental Toxicology and Risk Assessment 1993
DOI: 10.1520/stp19249s
|View full text |Cite
|
Sign up to set email alerts
|

From Research to Routine: A Review of Toxicity Testing with Marine Molluscs

Abstract: From the numerous and diverse studies of pollution effects on marine molluscs, a few species and techniques have emerged as suitable for routine effluent toxicity measurement. As marine mollusc toxicity testing evolves from research to routine application, it has become increasingly important to determine the reliability and repeatability of toxicity measurement, and to evaluate the degree of protection that regulations based on such measures provide for organisms that inhabit receiving waters. This paper revi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
21
0
1

Year Published

1996
1996
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 48 publications
2
21
0
1
Order By: Relevance
“…Acute hexazinone exposure had comparatively little impact on pediveliger mortality. These results are consistent with reports that even brief exposures to pesticides or other toxicants can reduce larval bivalve survival and growth (Davis and Hidu, 1969; Hunt and Anderson, 1993). …”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Acute hexazinone exposure had comparatively little impact on pediveliger mortality. These results are consistent with reports that even brief exposures to pesticides or other toxicants can reduce larval bivalve survival and growth (Davis and Hidu, 1969; Hunt and Anderson, 1993). …”
Section: Discussionsupporting
confidence: 92%
“…, reviewed by Hunt and Anderson, 1993), and embryo-larval development assays are widely used as sensitive indicators of toxicity, data concerning the susceptibility of soft-shell clam larvae to toxicants are sparse. Our laboratory experiments demonstrated pesticide and stage-specific differences in clam survival following 24h exposure to different concentrations of 2,4-D, hexazinone or phosmet.…”
Section: Discussionmentioning
confidence: 99%
“…While 29% of the samples were toxic to amphipods, 78% were toxic to abalone embryos (in 100% pore water). Although there are no published studies specifically designed to compare the relative sensitivity of the abalone and amphipod protocols, previous research using spiked water and sediment samples [32,34] and contaminated field samples [1,2] have indicated that amphipod and invertebrate embryo-larval protocols have variable sensitivity to contaminants. Dif-Sediment quality in Los Angeles Harbor Environ.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, Region 6 sought assistance from the USEPA National Exposure Research Laboratory in Cincinnati, Ohio (NERL), through the Regional Methods Initiative (RMI) Program, to conduct side-by-side C. dubia and P. promelas acute sediment elutriate toxicity tests. Interlaboratory tests can identify the effects of variation in chemical factors (i.e., dilution water and elutriate preparation), physical factors (i.e., test materials), and human factors (i.e., personnel and training), as well as the compounded effects of biological factors at each laboratory (Hunt and Anderson 1993). The objective of this study was to determine if any differences could be identified in the interlaboratory results of toxicity tests conducted independently by Region 6 and NERL on elutriate samples prepared from the same sediment samples using different elutriate preparation procedures.…”
Section: Introductionmentioning
confidence: 99%